2016
DOI: 10.1002/lary.26370
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and validation of a low-cost, medium-fidelity silicone injection molded endoscopic sinus surgery simulation model

Abstract: NA Laryngoscope, 127:781-786, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
49
0
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 23 publications
(27 reference statements)
0
49
0
2
Order By: Relevance
“…Another group developed a medium fidelity model that was shown to improve ESS skills among residents, but their model was difficult to build, as it was entirely molded by hand . More recently, 1 group developed a medium fidelity 3D‐printed model that was shown to be useful for basic endoscopic skills acquisition . Some factors may limit the use of these models, including need to assemble the model, inability to alter the anatomy, and the inability to perform a comprehensive ESS procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Another group developed a medium fidelity model that was shown to improve ESS skills among residents, but their model was difficult to build, as it was entirely molded by hand . More recently, 1 group developed a medium fidelity 3D‐printed model that was shown to be useful for basic endoscopic skills acquisition . Some factors may limit the use of these models, including need to assemble the model, inability to alter the anatomy, and the inability to perform a comprehensive ESS procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Three‐dimensional printing is being used in an increasing number of clinical and educational applications given its ability to create complex architecture in a rapid, reproducible fashion at reasonably low costs. Within otolaryngology, recent applications include scaffolds for microtia repair, nasal reconstruction, and tracheal grafts, as well as construction of sinus surgery simulators …”
Section: Discussionmentioning
confidence: 99%
“…Within otolaryngology, recent applications include scaffolds for microtia repair, nasal reconstruction, and tracheal grafts, as well as construction of sinus surgery simulators. 11,12…”
Section: Discussionmentioning
confidence: 99%
“…The Georgetown low-cost sinus trainer costs $5 and allows the trainee to practise basic endoscopy and sinus surgery skills including recess probing, targeted injections, removal of a suture, removal of a foreign body and antrostomy creation using an egg [19,20] University of Toronto developed a low-cost, low-idelity, easily constructed simulator for $20 with ive diferent training modules and demonstrated that training on the model had a positive impact on ESS skills [21,22]. More recently, the University of Texas [23] have produced a silicone injection moulded ESS simulation model at low cost and testing revealed high ratings for both face and construct validity. Storz have crafted a lifelike training model based on real computed tomography images.…”
Section: Simulationmentioning
confidence: 99%